Compensation and Work Motivation Effect on Teacher Performance at Baitul Makmur Foundation Malang - Antyanadea Maharani; Hadi Sunaryo; Agus Salim (Budapest International Research and Critics University, 2022)
This study aims to describe compensation, work motivation, and teacher performance as well as the effect of compensation on teacher performance both directly and indirectly through work motivation as an intervening variable, the sampling technique used in this study is a saturated sample, which uses the entire population as a sample at the Baitul Makmur Foundation teacher in Malang. The data analysis tool used is Structural Equation Modeling (SEM) analysis using the PLS version 3.0 application. Based on the results of data analysis shows that compensation has no effect on work motivation, while compensation has an effect on teacher performance at Baitul Makmur Foundation Malang, while work motivation is not able to mediate the effect of compensation on teacher performance at Baitul Makmur Foundation Malang.